Exosomal ncRNAs: The pivotal players in diabetic wound healing - Shen, Jiuheng; Zhao, Xian; Zhong, Youxiu; Yang, Peng; Gao, Peifen; Wu, Xue; Wang, Xudong; An, Wenlin (Frontiers in Immunology, 2022)
Diabetes is the most prevalent metabolic disease in the world today. In addition to elevated blood glucose, it also causes serious complications, which has a significant effect on the quality of life of patients. Diabetic trauma is one of complications as a result of the interaction of diabetic neuropathy, peripheral vascular disease, infection, trauma, and other factors. Diabetic trauma usually leads to poor healing of the trauma and even to severe foot ulcers, wound gangrene, and even amputation, causing serious psychological, physical, and financial burdens to diabetic patients. Non-coding RNAs (ncRNAs) carried by exosomes have been demonstrated to be relevant to the development and treatment of diabetes and its complications. Exosomes act as vehicle, which contain nucleic acids such as mRNA and microRNA (miRNA), and play a role in the intercellular communication and the exchange of substances between cells. Because exosomes are derived from cells, there are several advantages over synthetic nanoparticle including good biocompatibility and low immunogenicity. Exosomal ncRNAs could serve as markers for the clinical diagnosis of diabetes and could also be employed to accelerate diabetic wound healing via the regulation of the immune response and modulation of cell function. ncRNAs in exosomes can be employed to promote diabetic wound healing by regulating inflammation and accelerating re-vascularization, re-epithelialization, and extracellular matrix remodeling. Herein, exosomes in terms of ncRNA (miRNA, lncRNA, and circRNA) to accelerate diabetic wounds healing were summarized, and we discussed the challenge of the loading strategy of ncRNA into exosomes.